Valuation of ecosystem services- a case study of kolleru lake in andra pradesh - Eruva Mamatha (Department of Agricultural Economics, College of Horticulture, 2009)
Wetlands are one of the most productive ecosystems, comparable to tropical evergreen forests and play a significant role in the ecological sustainability. They are facing rapid decline in coverage and quality. The present study on “Valuation of ecosystem services-A case study of Kolleru Lake in Andhra Pradesh” was taken up with the objectives of identifying the services provided by the lake as perceived by the stakeholders and assessing the Willingness To Pay (WTP) for ecosystem services. It was conducted in one of the important wetland systems in India, Kolleru Lake in Andhra Pradesh, which is declared as a RAMSAR site.